Directed charge transfer in all solid state heterojunction of Fe doped MoS2 and C–TiO2 nanosheet for enhanced nitrogen photofixation. (November 2021) - Song, Qian; Sun, Congcong; Wang, Zheng; Bai, Xiaoxia; Wu, Keming; Li, Qiang; Zhang, Hui; Zhou, Lijun; Pang, Haili; Liang, Yanping; Yue, Shuai; Zhao, Zhenhuan
Abstract: Nitrogen photofixation to produce ammonia has mainly focused on the single photocatalyst leading to poor charge separation and limited reductive capability. In this work, we demonstrate an efficient all solid-state z-scheme heterojunction by immobilization of Fe doped MoS2 nanobundles on carbon coated porous TiO2 nanosheets, achieving a high yield of ammonia of 205.7 μg gcat −1 h −1 in ultrapure water without any sacrificial reagent under illumination. The z-scheme heterojunction has been compared with the designed p-n junction. It is found that the high performance is ascribed to at least three aspects. Firstly, the Fe doped MoS2 nanobundles provide multiple sites to surface nitrogen reduction reaction. Secondly, the z-scheme system has directed the flow of photocarriers, and hence electrons in high energy level of MoS2 can be utilized for the surface reduction reaction. Lastly, the charge transfer is significantly improved by the suppressed recombination of photogenerated electrons and holes in the z-scheme junction. The present study has provided a useful strategy to design active composite photocatalysts for nitrogen photofixation. Graphical abstract: Image 1 Highlights: Fe doped MoS2 nanobundles were developed with multiple active sites for nitrogen reduction reaction. An all solid-state Z-scheme heterojunction of Fe–MoS2 @C–TiO2 has been designed and prepared. Energetic electrons promote the nitrogen photofixation due to the directed charge transfer in the Z-scheme.